1996
DOI: 10.1021/np960405q
|View full text |Cite
|
Sign up to set email alerts
|

The Biotransformation of Two 3,15-Oxygenate ent-Kaurane Derivatives by Gibberella fujikuroi

Abstract: The incubation of 3α,15β-dihydroxy-ent-kaur-16-ene (1) with the fungus Gibberella fujikuroi gave 3α,7α,15β-trihydroxy-ent-kaur-16-ene (5), 3α,11β,15β-trihydroxy-ent-kaur-16-ene (13), and 3α,7α,11β,15β-tetrahydroxy-ent-kaur-16-ene (17). The ether 3α,15β-dihydroxy-11β,16β-epoxy-ent-kaurane (15) and the isomerized compounds 3α,7α-dihydroxy-15-oxo-ent-(16S)-kaurane (8) and 3α,7α,11β-trihydroxy-15-oxo-ent-(16S)-kaurane (10) were also obtained. The incubation of 3α-hydroxy-15-oxo-ent-(16S)-kaurane (7) with the fungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Fraga and co-workers [75,93] showed that the biotransformation of ent-15β,16β-dihydroxy-or ent-15β,16β-epoxy-kauranes by Gibberella fujikuroi produced selective hydroxylation at the ent-7β and ent-11α positions, and inhibited the oxidation of C-19. Similar results were also obtained in kauranes having the ent-16β,17-diol [94], ent-15α-hydroxyl or 15-oxo [95] groups. Besides, an ent-11α-hydroxylation seems to be directed by the presence of a 7-oxo group [96].…”
Section: Microbiological Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Fraga and co-workers [75,93] showed that the biotransformation of ent-15β,16β-dihydroxy-or ent-15β,16β-epoxy-kauranes by Gibberella fujikuroi produced selective hydroxylation at the ent-7β and ent-11α positions, and inhibited the oxidation of C-19. Similar results were also obtained in kauranes having the ent-16β,17-diol [94], ent-15α-hydroxyl or 15-oxo [95] groups. Besides, an ent-11α-hydroxylation seems to be directed by the presence of a 7-oxo group [96].…”
Section: Microbiological Methodssupporting
confidence: 82%
“…Besides, an ent-11α-hydroxylation seems to be directed by the presence of a 7-oxo group [96]. The non-oxidation of C-19 by this microorganism was also observed in kauranes having one ent-3β-hydroxyl or one carbonyl at C-3 [75,95].…”
Section: Microbiological Methodsmentioning
confidence: 67%
“…Transformation was carried out as previously described (Tudzynski et al, 1996). About 10 7 protoplasts were transformed with about 10 μg of the amplified replacement cassettes for generating the knock-outs.…”
Section: Methodsmentioning
confidence: 99%
“…2) H (8), and HÀC(8)/HÀC(7) indicated that they were on the same side of the molecule, and they were arbitrarily assigned as b-oriented. The correlations H a ÀC(2)/Me(14), Me(14)/ H a ÀC (9), and H a ÀC(9)/HÀC(11) indicated a-orientation. Thus, 2 is a rare natural ciseudesmane derivative [12].…”
mentioning
confidence: 99%
“…1) experiments provided the gross structure of 1 as a kaurane-type diterpenoid or its enantiomer [8] with a ketone and three OH groups. The HMBC of Me (17) (7) is a-oriented, and the OH groups at C(11) and C(14), and the Me group at C(16) are b-oriented, which was supported by the chemical shifts and splitting patterns of corresponding H-atoms [8] [9].…”
mentioning
confidence: 99%